2016
DOI: 10.1111/pde.12824
|View full text |Cite
|
Sign up to set email alerts
|

Plasmacytoid Dendritic Cells and Type I Interferon Signature in Lichen Striatus

Abstract: Background and aims Vd2 T cells have predominantly been investigated in tumour immuno-surveillance and the host defense against viral invasion. The precise role of Vd2 T cells in the pathogenesis of SLE remains elusive. Methods We measured the proportion of peripheral Vd2 T cells as well as the status and chemokine receptor expression profiles in SLE patients and healthy control (HC). In addition, Vd2 T cell infiltration in the kidneys of patients with lupus nephritis was examined. Results The percentage of pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
16
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 44 publications
1
16
0
4
Order By: Relevance
“…Fifth, tumour necrosis factor (TNF)‐α inhibitors, known to be secondary inducers of IFN‐α, have also been reported to induce PL . Finally, PL has been reported in association with several cutaneous inflammatory disorders, including psoriasis, alopecia areata, and lichen striatus, for which evidence suggests that pDCs play a significant role in their underlying pathogenesis …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Fifth, tumour necrosis factor (TNF)‐α inhibitors, known to be secondary inducers of IFN‐α, have also been reported to induce PL . Finally, PL has been reported in association with several cutaneous inflammatory disorders, including psoriasis, alopecia areata, and lichen striatus, for which evidence suggests that pDCs play a significant role in their underlying pathogenesis …”
Section: Discussionmentioning
confidence: 99%
“…Recently, much evidence has accumulated on the central role played by the pDCs and their product, type I IFNs, in several skin diseases characterized by the ID pattern. 6,[8][9][10][11] Initially, Fah et al reported high MxA expression not only in acute viral skin lesions, but also in autoimmune conditions with an ID pattern, such as LE and LP. 12 This indicated an activation of the type I IFN system in these autoimmune skin disorders.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Both lesions may appear over Blaschko and Sherrington lines, which brings out the question of a somatic mosaic origin . The lesions also may be induced by interferon therapy, and both present CD8 + T‐lymphocytes infiltrate . Cutaneous mosaicisms are clinical expressions of disorders that affect a mosaic area on the skin; this concept is a principle for understanding somatic mosaicism, which refers to the occurrence of two genetically distinct populations of cells within an individual derived from a postzygotic mutation.…”
Section: Discussionmentioning
confidence: 99%